ANALYZING THE IMPACT OF SOCIAL MEDIA INFLUENCERS ON CONSUMER BEHAVIOR: A COMPREHENSIVE LITERATURE REVIEW - Nicoleta ISAC (Revista de Management Comparat International)
In the digital era, companies rely on a strong digital presence to shape their reputation and engage consumers effectively. This study explores the impact of influencers on consumer behavior within the realm of digital marketing. The study employs a comprehensive literature review approach to delve into the dynamic interplay between digital influencers, consumer decisions, and brand promotion strategies. Through content analysis, this research aims to uncover the nuances of consumer interactions with influencers in the digital landscape, shedding light on the evolving nature of online marketing practices. The findings are expected to provide valuable insights for companies seeking to optimize their digital marketing strategies and effectively leverage the influence of digital leaders on consumer behavior.